Prospective Investors Perception on Investment Intention in Indonesia Sharia Stocks Market: A Conceptual Framework - Putri Dika, Riri (Advances in Social Sciences Research Journal, 2022)
Capital markets are an important component of the financial system, investment decisions are important for one’s future and these decisions are related to many factors. Investment is one of the teachings and concepts of Islam and the emergence of sharia stocks in the Indonesian capital market opens up opportunities for the Indonesian Muslim community to invest. As a country with the largest Muslim population globally, Indonesia is a country with the largest sharia capital market share globally. This should encourage and facilitate Islamic investors to invest in the Indonesian economy, especially the capital market. Yet the fact is, sharia stocks are still lower than the growth target The number of studies on the intention to invest in stocks in Indonesia which is relatively few led this study to try to test the influence of behavior on attitudes, subjective norms and behavioral control perceptions on the intention to invest in stocks. This research paper aims to study the perception of prospective investors on factors that will influence their investment intention in sharia stocks in the Indonesian Stock Exchange. This study uses the theory of planned behavior (TPB) with attitudes, subjective norms and behavioral control as independent variables. This study combines three critical things namely, attitudes, subjective norms and behavioral control of assumptions. This research adopted a quantitative method using questionnaire distribution and analyses using SEM-PLS. The results of the research will contribute to the field of management and consumer behavior in decision making to investment. From this research, Indonesians can know and invest in the Indonesian stock market, especially sharia stocks. Research also contributes to the development of knowledge in the field of finance that focuses on investor behavior. Keywords: Attitude, Subjective Norms, Behavior Control, Intention, Sharia Stocks, TPB